Cutaneous Metastasis of Prostate Adenocarcinoma: A Rare Presentation of a Common Disease - Dills, Alexander (J Investig Med High Impact Case Rep, 2021)
Prostate cancer is the most common cancer affecting men in the United States and the second greatest cause of cancer-related death. Metastases usually occur to bone followed by distant lymph nodes and then viscera. Cutaneous metastases are extremely rare. Their presence indicates advanced disease and a poor prognosis. As they are highly variable in appearance and may mimic a more benign process, biopsy is essential for identification. Serine proteases, particularly human tissue kallikreins, may play an important role in promoting metastasis and facilitate infiltration of the skin. Individual cancer genetics may predispose to more aggressive cancer and thus earlier and more distant metastases. In this article, we report our case of a 67-year-old man with a 4-year history of castrate-resistant prostate cancer with cutaneous metastases confirmed by histology. Despite multiple lines of systemic therapy, the patient suffered progressive disease with worsening performance status and was enrolled in hospice.